Public Wi-Fi: Space, sociality and the social good - Lambert, Alex; McQuire, Scott; Papastergiardis, Nikos (Journal of Telecommunications and the Digital Economy, 2020)
Public Wi-Fi services are rolling out across Australia, with city councils and telcos building large-scale networks in urban areas. Questions as to the value of public Wi-Fi have never been more significant in the Australian context. In this article we explore how free Wi-Fi services offered by cultural institutions and municipalities influence public spaces, and ask how such services can engender practices which promote the social good. Drawing on ethnographic research into six Wi-Fi equipped spaces in Victoria, we find a variety of issues which influence whether a service will be popular and hence have a significant influence on public space. Services which are popular enable a range of uses, and this can add to the appeal and atmosphere of a space. However, Wi-Fi has yet to truly facilitate the kind of social interactions and rich civic placemaking we associate with the social good.